Medical conditions in the athlete - Cuppett, Micki; Flanagan, Katie Walsh (Champaign, IL Human Kinetics, 2017)
Medical Conditions in the Athlete, Third Edition With Web Study Guide provides comprehensive medical information that assists health care providers and athletic trainers in recognizing and identifying underlying and potentially serious medical conditions that may affect their chosen course of treatment. The book addresses medical conditions by body system, their mechanism of acquisition, signs, symptoms, differential diagnoses, referral, treatment, and return-to-participation criteria. Also provides readers with research-driven assessment and treatment information for medical conditions that affect all types of athletes. It is a comprehensive textbook and an important reference for health care providers such as athletic trainers and physical therapists who work with active populations.
Introduction to medical conditions -- Medical examination -- Diagnostic imaging and testing -- Basic principles of pharmacology -- Therapeutic drug categories -- Common procedures and interventions in the athletic training clinic -- Respiratory system -- Cardiovascular system -- Gastrointestinal system -- Genitourinary and gynecological systems -- Neurological system -- The eye -- Ear, Nose, Throat, and Mouth -- Systemic disorders -- Infectious diseases -- Dermatological conditions -- Psychological and substance use disorders -- Working with special populations.
Preceded by General medical conditions in the athlete / Micki Cuppett, Katie M. Walsh. 2nd ed. c2012.
Author's names reversed on previous editions.
"Includes a web study guide with 18 case studies and 109 questions"--Cover.
Includes bibliographical references and index.
Keywords: Sports medicine; Sports injuries -- Diagnosis; Sports injuries -- Treatment